"Med‐Arb": Behind the Closed Doors of a Hybrid Process. (21st October 2013) - Barsky, Allan
<x xml:space="preserve">Abstract</x> Med‐arb is a hybrid conflict resolution process that attempts to blend the collaborative, client‐empowering approach of mediation with the efficiency and finality of decision making from arbitration. This article explores the benefits and risks of med‐arb in the context of separation‐divorce cases. The conclusions offer suggestions for maximizing the benefits and managing the risks. Keypoints for the Family Court Community Many conflict resolution practitioners are blending the roles and skills of different conflict resolution processes in order to better serve the needs of different clients. Although blending roles and skills may provide certain advantages, practitioners and program developers need to be cognizant of unintended consequences. This article highlights the risks of blending mediation and arbitration in relation to client self‐determination, informed consent, fairness, neutrality, power, and other issues.